(untitled) (Revista de Ciências Agroveterinárias, 2016)
Scarabaeinae (Coleoptera: Scarabaeidae), comprises the beetles popularly called “dung beetle”, which are important group of animal detritivorous and biomarkers of environmental impacts on ecosystems. Pampa Biome areas are natural ecosystems with high diversity of plant and animal species, but are however, little known compared to other biomes of Brazil. Data on escarabeinofauna the Pampa Biome is scarce. Therefore, the aim of this study was to inventorize the fauna of these beetles in areas located in the far south of the Rio Grande do Sul, as well as learning their habits and eating behaviors. The sampling areas were located in the cities of Herval and Arroio Grande. 216 traps baited pitfall trap type with human dung and pig and beef decaying were placed distributed in six areas. They recorded 2,243 individuals, organized into six tribes, 13 genera and 35 species. The species were classified as coprophagous, general and scavenger. Greater number of subjects were caught in traps baited with human and pig manure than in rotting meat. For the first time Trichillum morelli Verdú & Galante, 1997 was found in Brazil and Canthidium taurinum Harold, 1867 is a new record for the state.